Hyperoxia affects the lung tissue: A porcine histopathological and metabolite study using five hours of apneic oxygenation - Sigríður Olga Magnúsdóttir; Raluca Georgiana Maltesen; Lise Haugaard Banch; Ulrik Thorngren Baandrup; Heidi Valbjørn; Trygve Andreassen; Tone Frost Bathen; Bodil Steen Rasmussen; Benedict Kjærgaard (Metabolism Open, 2019)
Background: Oxygen is a liberally dosed medicine; however, too much oxygen can be harmful. In certain situations, treatment with high oxygen concentration is necessary, e.g. after cardiopulmonary resuscitation. The amount of oxygen and duration of hyperoxia causing pulmonary damage is not fully elucidated. The aim of this study was to investigate pathophysiological and metabolite changes in lung tissue during hyperoxia while the lungs were kept open under constant low pressure. Methods: Seven pigs were exposed to 100% oxygen for five hours, using an apneic oxygenation technique with one long uninterrupted inspiration, while carbon dioxide was removed with an interventional lung assist. Arterial blood samples were collected every 30 minutes. Lung biopsies were obtained before and after hyperoxia. Microscopy and high-resolution magic angle spinning nuclear magnetic resonance spectroscopy were used to detect possible pathological and metabolite changes, respectively. Unsupervised multivariate analysis of variance and paired sample tests were performed. A two-tailed p-value ≤ 0.05 was considered significant. Results: No significant changes in arterial pH, and partial pressure of carbon dioxide, and no clear histopathological changes were observed after hyperoxia. While blood glucose and lactate levels changed to a minor degree, their levels dropped significantly in the lung after hyperoxia (p ≤ 0.04). Reduced levels of antioxidants (p ≤ 0.05), tricarboxylic acid cycle and energy (p ≤ 0.04) metabolites and increased levels of several amino acids (p ≤ 0.05) were also detected. Conclusion: Despite no histological changes, tissue metabolites were altered, indicating that exposure to hyperoxia affects lung tissue matrix on a molecular basis. Keywords: Apneic oxygenation, Hyperoxia, Lung tissue, Histopathology, Porcine model, Metabolites